The Effect of Debt Default, Prior Loss, and Prior Opinion on Going Concern Audit Opinion - Aulia, Faiza Hikma; Andayani, Wuryan (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to empirically prove the effect of debt default, prior loss, and prior opinion on the acceptance of a going-concern audit opinion based on agency theory. This study applies a quantitative approach, involving samples of 204 infrastructure companies listed on the Indonesia Stock Exchange in 2020-2023, selected based on established criteria through purposive sampling. The results of the logistic regression analysis show that the default of debt does not affect the acceptance of a going-concern audit opinion. In contrast, prior loss and prior opinion have a significant positive impact on the acceptance of a going-concern audit opinion.